2007
DOI: 10.1002/mds.21706
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and tea consumption and the risk of Parkinson's disease

Abstract: Several prospective studies have assessed the association between coffee consumption and Parkinson's disease (PD) risk, but the results are inconsistent. We examined the association of coffee and tea consumption with the risk of incident PD among 29,335 Finnish subjects aged 25 to 74 years without a history of PD at baseline. During a mean follow-up of 12.9 years, 102 men and 98 women developed an incident PD. The multivariate-adjusted (age, body mass index, systolic blood pressure, total cholesterol, educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
151
1
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(165 citation statements)
references
References 39 publications
9
151
1
4
Order By: Relevance
“…The Leisure World cohort study and a Finnish cohort study reported no associations [434,481]. In the Health Professionals Follow-up Study [478], there was an inverse association between tea intake and PD in men who did not drink coffee (RR 0.4, 95% CI 0.2-1.2 for more than one cup per day versus none, p for trend 0.02), but no association in women.…”
Section: Coffee and Teamentioning
confidence: 94%
See 1 more Smart Citation
“…The Leisure World cohort study and a Finnish cohort study reported no associations [434,481]. In the Health Professionals Follow-up Study [478], there was an inverse association between tea intake and PD in men who did not drink coffee (RR 0.4, 95% CI 0.2-1.2 for more than one cup per day versus none, p for trend 0.02), but no association in women.…”
Section: Coffee and Teamentioning
confidence: 94%
“…One study based on residents in five geographic areas of Finland reported a hazard ratio (HR) of 0.40 (95% CI 0.23-0.71) for five cups of coffee per day or more versus none (p for trend 0.005) [481]. The Finnish Mobile…”
Section: Coffee and Teamentioning
confidence: 99%
“…PIDEMIOLOGICAL studies have indicated that coffee consumption may be protective in Alzheimer's (AD) (Barranco Quintana et al 2007) and Parkinson's diseases (PD) (Hu et al 2007). Although a universal consensus on the cause(s) of Alzheimer's disease has not been reached, the best-supported hypotheses posit that accumulation of the b-amyloid peptide (Ab) is central to the induction of Alzheimer's disease pathology.…”
mentioning
confidence: 99%
“…The same risk for the population who drank 4-6 cups of green tea per week (or 1 cup green tea daily) was 38% lower than that in the population who did not drink tea (Kuriyama et al, 2006). A survey conducted in USA indicated that the risk of PD in the population who drank 2 cups or more of tea per day was decreased (Hu et al, 2007).…”
Section: Prevention Of Neurodegenerative Diseasesmentioning
confidence: 99%